2014
DOI: 10.15845/on.v37i0.608
|View full text |Cite
|
Sign up to set email alerts
|

Has climate change resulted in a mismatch between the spring arrival of the Common Cuckoo Cuculus canorus and its hosts in North Norway?

Abstract: Abstract. Analyses of arrival dates of the common cuckoo and four of its hosts in North Norway since 1980 found no evidence of a climate-driven mismatch that might contribute to the decline in the Norwegian cuckoo population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…day 1 = 1 January) prior to analysis. The relative annual advancement in dates of the arrival of cuckoo species, their hosts and prey emergence was estimated by calculating the difference between the arrival date of each cuckoo species and the arrival/emergence date of their host and prey species, respectively [ 14 , 34 ]; we used this as an index of potential temporal phenological asynchrony/mismatch. If cuckoos would show smaller advancement in their arrival than their hosts, they may miss the opportunity to check thoroughly territories occupied by potential hosts and lay parasitic eggs because the optimal time for parasitation is very short [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…day 1 = 1 January) prior to analysis. The relative annual advancement in dates of the arrival of cuckoo species, their hosts and prey emergence was estimated by calculating the difference between the arrival date of each cuckoo species and the arrival/emergence date of their host and prey species, respectively [ 14 , 34 ]; we used this as an index of potential temporal phenological asynchrony/mismatch. If cuckoos would show smaller advancement in their arrival than their hosts, they may miss the opportunity to check thoroughly territories occupied by potential hosts and lay parasitic eggs because the optimal time for parasitation is very short [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sin embargo, los desajustes fenológicos observados en el críalo europeo (Clamator glandarius) no parecen deberse a la respuesta de sus hospedadores a las condiciones climáticas (Avilés et al 2014). Tampoco es el caso del cuco común en Noruega, donde se mostró su llegada anticipada a las zonas de reproducción pero no la de sus hospedadores, por lo que no se encontró evidencia de que cambios en el clima provocasen un desajuste fenológico entre el parásito y sus hospedadores que contribuyera a la disminución de su población (Barrett 2014).Los efectos en las fenologías de los diferentes organismos mencionados debidos al cambio climático se resumen en la tabla 2.…”
Section: Efectos Del Clima Sobre Los Ajustes De Los Ciclos Vitales De Los Parásitosunclassified
“…It has therefore been hypothesized that the climate change has a greater influence on the Meadow Pipit migration than on cuckoo migration (Møller et al 2010, Møller 2011. As a result, the Meadow Pipit may start to lay eggs earlier, and could accordingly become a less suitable host because the cuckoo would arrive too late to utilize them (Saino et al 2009, Barrett 2014. This hypothesis has received some support from Møller et al (2010), who found that long-distance migrants at present are relatively more used by cuckoos than short-distance migrants.…”
Section: Introductionmentioning
confidence: 99%